Development Arduino Data Logger using INA219 Sensor for Battery Capacity Monitoring - Hollanda Arief Kusuma; Rifki Ariandhi; Septia Refly; Sapta Nugraha (Jurnal Teknik Elektro dan Komputasi (ELKOM), 2023)
A battery, also known as an accumulator, is an electrical cell that can reverse an electrochemical process with high efficiency. It is essential in the use of electrical systems as storage devices. It has two critical parameters: current and voltage. These parameters can affect the battery's behavior, which leads to battery usage. As a result, a battery monitoring instrument is required to monitor the battery's current and voltage while it is in use. The researchers designed a monitoring instrument with an Arduino Pro Mini 5V microcontroller as the main processor, INA219 as a current and voltage sensor, RTC DS3231 as a time reader, micro SD card module as a data logger, and OLED SH1106 to display the current, voltage, and time readings. The calibration of the INA219 sensor has a current reading accuracy of 91.43% and a voltage reading accuracy of 99.87%. RMSE was measured at 227.65 mA and 0.0146 V. The device was tested with a BSB DB 12-55Ah battery connected to 30W PJU lamps. In the results of this test, we experienced voltage drop and current ripple in the battery performance. The battery usage capacity was 49.71 Ah. Based on this research, the device built can monitor battery conditions.